The role of long-term target and masker talker familiarity in children’s speech-in-speech recognition - Flaherty, Mary M. (Frontiers in Psychology, 2024)
Objectives This study investigated the influence of long-term talker familiarity on speech-in-speech recognition in school-age children, with a specific emphasis on the role of familiarity with the mother’s voice as either the target or masker speech. Design Open-set sentence recognition was measured adaptively in a two-talker masker. Target and masker sentences were recorded by the adult mothers of the child participants. Each child heard sentences spoken by three adult female voices during testing; their own mother’s voice (familiar voice) and two unfamiliar adult female voices. Study sample Twenty-four school age children (8–13 years) with normal hearing. Results When the target speech was spoken by a familiar talker (the mother), speech recognition was significantly better compared to when the target was unfamiliar. When the masker was spoken by the familiar talker, there was no difference in performance relative to the unfamiliar masker condition. Across all conditions, younger children required a more favorable signal-to-noise ratio than older children. Conclusion Implicit long-term familiarity with a talker consistently improves children’s speech-in-speech recognition across the age range tested, specifically when the target talker is familiar. However, performance remains unaffected by masker talker familiarity. Additionally, while target familiarity is advantageous, it does not entirely eliminate children’s increased susceptibility to competing speech.